Effective means of the intervention health education for prevention of respiratory infection among Hajj pilgrims: Systemic review 2024 (The Review of Diabetic Studies, 2024)
BackgroundThe Islamic Hajj pilgrimage to Mecca is one of the world's largest annual mass gatherings. Inevitable overcrowding during the pilgrims' stay greatly increases the risk of acquiring and spreading infectious diseases, especially respiratory diseases. Factors contribute to high prevalence of respiratory disease among AL hajj pilgrims include physical exhaustion, sleep deprivation, and heat stress, inevitable overcrowding, both in housing and ritual sites.  The prevalence of respiratory illness has continued to surge among Hajj pilgrims from different countries despite having some practices of preventive measures. Respiratory illnesses during Hajj could be due to many reasons and many factors that promote disease spread. These factors include overcrowding, cigarette smoking, and direct contact with infectious agents particularly viruses promote the spread of respiratory infections. However, due to the longer duration of the pilgrimage, there are high chances of pilgrims contracting various respiratory illnesses due to exposure to respiratory pathogens.Aim of this systematically reviews: To determine the effective of the implemented the intervention health education to help prevent respiratory tract infections during Hajj. in Saudi Arabia2024.Method: The MEDLINE/PubMed and Scopus databases were searched for all relevant papers published prior to  2018 to 2024 that evaluated the prevalence of clinical symptoms of respiratory infections, including pneumonia among Hajj pilgrims, as well as their influenza and pneumococcal vaccination status Results: The Saudi health authority has recommended annual seasonal influenza vaccination during each Hajj season to curtail the risk of spreading respiratory tract infections as far back as the 2005 Hajj season especially for those at high risk of influenza and other respiratory tract complications Conclusion: Large multinational follow-up studies are recommended for clinic, Hajj pilgrims’ knowledge, attitudes, and practices toward respiratory tract infections are used as the determinant of the effectiveness of the health education interventions. Knowledge and application of basic hygiene principles, use of face masks, following cough etiquettes, engaging in social distancing, and engaging in other measures are highly important .